Navigating Determinants of India’s Business Relations with GCC Countries : Evidence from the Gravity Model Theory - Singh, Raj Kumar; Kumar, Ajay; Kumari, Jyoti; Singh, Yashvardhan (Prabandhan: Indian Journal of Management, 2022)
This research paper examined the determinants of India’s business relations with Gulf Cooperation Council countries from 1995 – 2019 using the gravity model theory based on the theoretical underpinning of Nobel Laureate Jan Tinbergen. The study focused on identifying variables that influenced India’s trade with GCC countries along with predicting the trade potential. The empirical findings were obtained through the random-effects model and fixed effects model. The Hausman test suggested that the random-effects model was more appropriate than the fixed effect model. The findings of the study stated that the GDP of India, GDP of Gulf countries, the population of Gulf countries, India’s economic integration with the world, India’s economic integration with GCC, trading affinity, and diaspora had a positive and significant impact on India’s bilateral trade relations with GCC, while foreign direct investment had a positive and insignificant impact. The analysis further revealed that distance, terms of trade, exchange rate, and language had a negative and significant effect on bilateral trade relations. The market size of the host country had a negative but insignificant impact on India’s trade with GCC. India has trade potential with Bahrain and Kuwait, while India has overtraded other GCC countries. The negative value of the coefficient of convergence of actual trade and potential trade indicated a lack of equilibrium in India’s estimated trade flows with GCC countries, but the insignificant p-value did not support the argument. A strong economic tie with GCC will boost the Indian industry and offer a strategic edge internationally.